GAMBARAN TINGKAT PENGETAHUAN, SIKAP DAN KEPATUHAN KONSUMSI TABLET TAMBAH DARAH PADA IBU HAMIL DI PUSKESMAS KEBUN KOPI KOTA JAMBI TAHUN 2023 - Analita, Maulina; Aurora, Wahyu Indah Dewi; Rahmatilah, Imat (LPPM Universitas Jambi, 2024)
Background: Based on data from health center performance assessment reports (PKP), data coverage of the achievement of the TTD program for pregnant women in the working area of ​​Kebun Kopi Health Center has a target of 62%, whereas from PKP data from January to June 2023 it is only 46.38% . There is no data on the number of pregnant women who consume TTD of at least 90 tablets. To identify problems related to knowledge, attitudes and compliance with TTD consumption among pregnant women towards the low achievement of the TTD program at the coffee plantation health center.Objective: To identify problems related to knowledge, attitudes and compliance with TTD consumption among pregnant women towards the low achievement of the TTD program at the coffee plantation health center.Method: This research is descriptive research using a mix method in the form of interviews and questionnaires. Interviews were conducted with KIA and Nutrition program officers. Questionnaires were given to all pregnant women who visited the Kebun Kopi Health Center.Results: The sample of this research consisted of 30 people. With the characteristics of most respondents aged 21-29 years (70%), the highest level of education was high school (57%), number of children > 1 (53%), and not working (73%). Have good knowledge about blood supplement tablets (57%), with poor attitudes about blood supplement tablets (53%) and mothers who have poor compliance (60%). Officers who hold the program only provide education when pregnant women take medicine, never provide counseling, communication with cadres also does not run smoothly.Conclusion: The problems faced are that the attitude of pregnant women regarding the consumption of TTD during pregnancy is still lacking, the compliance of pregnant women in consuming TTD during pregnancy is still lacking, there is no routine monitoring to monitor compliance with taking TTD medication in pregnant women, pregnant women often forget to consume TTD, mothers Pregnant women do not want to consume TTD because of the side effect of nausea after consuming TTD, there is no interesting promotional media about the importance of consuming TTD and the achievement of the TTD program for pregnant women at the coffee plantation health center is still lacking.